NANOFIBERS BASED ON CHITOSAN AND SYNTHETIC POLYMERS: A REVIEW OF PROPERTIES AND APPLICATIONS - Tajibayeva, Nasiba; Ergashev, Oybek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This review article is devoted to chitosan-based nanofibers combined with synthetic polymers—promising materials with a wide range of applications in biomedicine, filtration, and food packaging. Modern methods for producing such fibers are described, particularly electrospinning, as well as the influence of polymer composition on morphology, mechanical properties, solubility, water resistance, hydrophilicity, and thermal stability. The main application areas are reviewed: medical dressings, drug delivery systems, filtration membranes, and biodegradable packaging. Special attention is given to the role of synthetic polymers in improving technological and functional characteristics.